HUBUNGAN PEMANFAATAN LABORATORIUM BAHASA SEBAGAI SUMBER BELAJAR DENGAN MOTIVASI SISWA BERKOMUNIKASI BAHASA JEPANG : Studi Deskriptif Korelasional Terhadap SiswaKelas X Di SMAN 2 Bandung - Gumelar, Dwi Litania (2014)
Masalahpokokdalampenelitianiniadalah,hubunganantarapemanfaatanLaboratoriumBahasasebagaisumberbelajardenganmotivasisiswaberkomunikasiBahasaJepang.Adapunsecararincipenelitianberusahauntukmengetahuihubungan yangpositifdansignifikanantarapemanfaatanLaboratoriumBahasasebagaisumberbelajardenganmotivasisiswaberkomunikasiBahasaJepang, padaaspekmenyimak, berbicara, membacadanmenulis.Metode yang digunakan pada penelitian inistudideskriptifdenganjeniskorelasional.Berdasarkanperolehan data daripenelitianinimenunjukkan terdapat hubungan yang signifikan antara pemanfaatan laboratorium bahasa sebagai sumber belajar dengan motivasi siswa berkomunikasi Bahasa Jepang.Secarakhusus, kesimpulandalam penelitianini dapatdiuraikansebagaiberikut: (1) Terdapat hubungan yang positif dan signifikanantarapemanfaatanLaboratoriumBahasasebagaisumberbelajardenganmotivasisiswaberkomunikasiBahasaJepangpadaaspekmenyimaksebesar 0.938%, (2) Terdapat hubungan yang positif dan signifikanantarapemanfaatanLaboratoriumBahasasebagaisumberbelajardenganmotivasisiswaberkomunikasiBahasaJepangpadaaspekberbicarasebesar 0.969%, (3) Terdapat hubungan yang positif dan signifikanantarapemanfaatanLaboratoriumBahasasebagaisumberbelajardenganmotivasisiswaberkomunikasiBahasaJepangpadaaspekmembacasebesar 0.434%, (4) Terdapat hubungan yang positif dan signifikanantarapemanfaatanLaboratoriumBahasasebagaisumberbelajardenganmotivasisiswaberkomunikasiBahasaJepangpadaaspekmenulissebesar 0.878%. The main issue in this study is the relationship between the use of language laboratory as a source of learning and students' motivation to communicate using Japanese. The detailed study aimed to determine the positive and significant relation between the use of language laboratory as a source of learning and students' motivation to communicate using Japanese, on the aspect of listening, speaking, reading and writing.The method used in this study was a descriptive study with the correlation type. Based on data collected from this study showed a significant correlation between the use of the language laboratory as a source of learning and students' motivation to communicate using Japanese. In particular, the conclusions in this study can be described as follows: (1) There is a positive and significant relationship between the use of language laboratory as a source of learning and students' motivation to communicate using Japanese on the aspect of listening at 0.938%, (2) There is a positive and significant relationship between the use of language laboratory as a source of learning and students' motivation to communicate using Japanese on the aspect of speaking at 0.969%, (3) There is a positive and significant relationship between the use of language laboratory as a source of learning and students' motivation to communicate using Japanese on the aspect of reading at 0.434%, (4) There is a positive and significant relationship between the use of language laboratory as a source of learning and students' motivation to communicate using Japaneseon the aspect of writing at 0.878%.